Preparing of Cadmium Sulfide Nanoparticles and Studding their Optical and Structural Properties (International Journal of Scientific Research in Science and Technology, 2024)
Thin films of cadmium sulfide CdS have been deposited on glass substartes through chemical bath deposition, the films was examined using UV-Visible spectrometer and x-ray spectroscopy. the calculation of the energy gap show that it increases with deposition temperature and the x ray spectrum show also that the grain size decreases with deposition temperature, where the minimum grain size recorded was 26.17nm.